Individuals With Weaker Antibody Responses After Booster Immunization Are Prone to Omicron Breakthrough Infections - Möhlendick, Birte; Čiučiulkaitė, Ieva; Elsner, Carina; Anastasiou, Olympia E.; Trilling, Mirko; Wagner, Bernd; Zwanziger, Denise; Jöckel, Karl-Heinz; Dittmer, Ulf; Siffert, Winfried (Frontiers in Immunology, 2022)
Background: Despite the high level of protection against severe COVID-19 provided by the currently available vaccines some breakthrough infections occur. Until now, there is no information whether a potential risk of a breakthrough infection can be inferred from the level of antibodies after booster vaccination. Methods: Levels of binding antibodies and neutralization capacity after the first, one and six month after the second, and one month after the third (booster) vaccination against COVID-19 were measured in serum samples from 1391 healthcare workers at the University Hospital Essen. Demographics, vaccination scheme, pre-infection antibody titers and neutralization capacity were compared between individuals with and without breakthrough infections. Results: The risk of developing an Omicron breakthrough infection was independent of vaccination scheme, sex, body mass index, smoking status or pre-existing conditions. In participants with low pre-infection anti-spike antibodies (≤ 2641.0 BAU/ml) and weaker neutralization capacity (≤ 65.9 %) against Omicron one month after the booster vaccination the risk for developing an Omicron infection was 10-fold increased (P = 0.001; 95% confidence interval, 2.36 - 47.55). Conclusion: Routine testing of anti-SARS-CoV-2 IgG antibodies and surrogate virus neutralization can quantify vaccine-induced humoral immune response and may help to identify subjects who are at risk for a breakthrough infection. The establishment of thresholds for SARS-CoV-2 IgG antibody levels identifying “non”-, “low” and “high”-responders may be used as an indication for re-vaccination.